Diversity and structural analysis of rhizosphere soil microbial communities in wild and cultivated Rhizoma Atractylodis Macrocephalae and their effects on the accumulation of active components - Song,Pingping; Liu,Junling; Huang,Peng; Han,Zhili; Wang,Dianlei; Sun,Nianxia (PeerJ, 2023)
Rhizosphere microorganisms are the main factors affecting the formation of high quality medicinal materials and promoting the accumulation of secondary metabolites. However, the composition, diversity, and function of rhizosphere microbial communities in endangered wild and cultivated Rhizoma Atractylodis Macrocephalae (RAM) and their relationships with active component accumulation have remained unclear. In this study, high-throughput sequencing and correlation analysis were used to study the rhizosphere microbial community diversity (bacteria and fungi) of three RAM species and its correlation with the accumulation of polysaccharides, atractylone, and lactones (I, II, and III). A total of 24 phyla, 46 classes, and 110 genera were detected. The dominant taxa were Proteobacteria, Ascomycota, and Basidiomycota. The microbial communities in both wild and artificially cultivated soil samples were extremely species-rich, but there were some differences in their structure and the relative abundances of microorganism taxa. Meanwhile, the contents of effective components in wild RAM were significantly higher than those in cultivated RAM. Correlation analysis showed that 16 bacterial and 10 fungal genera were positively or negatively correlated with active ingredient accumulation. These results showed that rhizosphere microorganisms could play an important role in component accumulation and might lay a foundation for future research on endangered materials.
Keywords: Rhizoma Atractylodis Macrocephalae; Wild and cultivated; Rhizosphere microbial community; Rhizosphere fungi; Bacterial community; Root chemical composition accumulation